1992
DOI: 10.1111/j.1365-2710.1992.tb00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies and loss of periodontal bone in patients with rheumatoid arthritis

Abstract: Tolo K and Jorkjend L: Serum antibodies and loss of periodontal bone in patients with rheumatoid arthritis. J Clin Periodontol 1990; 17: 288-291. Abstract. The number of teeth, % of alveolar bone loss, serum IgG, and serum antibodies to Bacteroides gingivalis, Capnocytophaga ochracea and Eubacterium saburreum were recorded in 37 patients diagnosed with rheumatoid arthritis (RA) and in an age-and sex-matched control group of 37 individuals free from RA. The RA group had a significantly increased loss of teet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 13 publications
4
47
0
3
Order By: Relevance
“…RA and CP have remarkably similar pathobiology 9,12,35 . Studies evaluating the association between CP and RA were conducted, but the findings were inconsistent 8,23,34,36‐40 . These differences may be arising from different study designs and different disease classifications.…”
Section: Discussionmentioning
confidence: 99%
“…RA and CP have remarkably similar pathobiology 9,12,35 . Studies evaluating the association between CP and RA were conducted, but the findings were inconsistent 8,23,34,36‐40 . These differences may be arising from different study designs and different disease classifications.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum concentrations for immunoglobulins could be an indication of an increased humoral response to arthritogenic antigens. Tolo & Jorkjend (1990) reported that the total serum IgG as well as specific IgG antibodies to Bacteroides gingivalis and Eubacterium saburreum influenced the degree of alveolar bone loss in patients with RA. In the present study, there was no significant difference between the means of SBI and CAL depending on the serum levels for IgA, IgG and IgM.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, the interrelationship between RA and periodontitis (PD) has become increasingly appreciated (5). Several studies have shown an increased frequency of periodontitis (PD) in patients with RA compared to individuals without RA (6-9). It also has been found that measures of RA disease severity (e.g.…”
Section: Introductionmentioning
confidence: 99%